The implementation of public policies for human rights education in different countries - Sousa, Rodger Roberto Alves de; Carth, James Land (Revista Interseção, 2025)
ABSTRACT The implementation of public policies for human rights education is a fundamental strategy for promoting a culture of respect and appreciation of human rights in different countries. This systematic literature review analyzed the main characteristics, challenges, and results of implementing public policies for human rights education in various national contexts, as well as the role of schools and civil society in this process. The results point to the importance of integrating human rights education at all levels of education and the need for a multidisciplinary and participatory approach to its implementation. Additionally, the role of international organizations in promoting and supporting the implementation of public policies for human rights education in different countries was highlighted. The implementation of these policies was also identified as a fundamental strategy for preventing violence and discrimination. However, challenges in implementation, such as the lack of financial and human resources, resistance from certain groups, and a lack of evaluation of results were identified. These challenges must be addressed to achieve the effectiveness of public policies for human rights education and advance the construction of more just and democratic societies. Keywords: Public policies. Human rights education. Schools. Civil society. Violence prevention. A implementação de políticas públicas de educação em direitos humanos em diferentes países RESUMO A implementação de políticas públicas de educação em direitos humanos é uma estratégia fundamental para a promoção de uma cultura de respeito e valorização dos direitos humanos em diferentes países. Esta revisão sistemática da literatura analisou as principais características, desafios e resultados da implementação de políticas públicas de educação em direitos humanos em diversos contextos nacionais, bem como o papel das escolas e da sociedade civil nesse processo. Os resultados apontam para a importância da integração da educação em direitos humanos em todos os níveis de ensino e para a necessidade de uma abordagem multidisciplinar e participativa na sua implementação. Além disso, foi destacado o papel dos organismos internacionais na promoção e apoio à implementação de políticas públicas de educação em direitos humanos em diferentes países. A implementação dessas políticas também foi apontada como uma estratégia fundamental de prevenção da violência e da discriminação. No entanto, foram identificados desafios na implementação, como a falta de recursos financeiros e humanos, a resistência de certos grupos e a falta de avaliação dos resultados. É necessário enfrentar esses desafios para alcançar a efetividade das políticas públicas de educação em direitos humanos e avançar na construção de sociedades mais justas e democráticas. Palavras-chave: Políticas públicas. Educação em direitos humanos. Escolas. Sociedade civil. Prevenção da violência.